2022
DOI: 10.1021/acs.nanolett.2c01439
|View full text |Cite
|
Sign up to set email alerts
|

Exsolution-Driven Surface Transformation in the Host Oxide

Abstract: Exsolution synthesizes self-assembled metal nanoparticle catalysts via phase precipitation. An overlooked aspect in this method thus far is how exsolution affects the host oxide surface chemistry and structure. Such information is critical as the oxide itself can also contribute to the overall catalytic activity. Combining X-ray and electron probes, we investigated the surface transformation of thin-film SrTi0.65Fe0.35O3 during Fe0 exsolution. We found that exsolution generates a highly Fe-deficient near-surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 50 publications
4
39
0
Order By: Relevance
“…In the modeling, we set d * = 2 nm. This is because we have recently shown that the Fe atoms in the surface exsolved Fe 0 nanoparticles on STF are mainly extracted from a very thin layer (∼2 nm) near the STF surface, while the bulk of the STF film was not affected . Finally, c is a constant coefficient that accounts for the stoichiometric relationship between the metal cations and oxygen anions.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…In the modeling, we set d * = 2 nm. This is because we have recently shown that the Fe atoms in the surface exsolved Fe 0 nanoparticles on STF are mainly extracted from a very thin layer (∼2 nm) near the STF surface, while the bulk of the STF film was not affected . Finally, c is a constant coefficient that accounts for the stoichiometric relationship between the metal cations and oxygen anions.…”
Section: Theorymentioning
confidence: 99%
“…To examine this hypothesis, we chose single-crystalline thin-film SrTi 0.65 Fe 0.35 O 3 (STF) as a model system. Previous studies have shown that STF is a promising electrode material in solid oxide fuel cells and electrolysis cells that can exsolve metallic iron (Fe 0 ) nanoparticles as catalysts to enhance water splitting kinetics . In this study, we begin by presenting an analytical kinetic model, which shows that the oxygen release kinetics in thin-film STF are dependent on both the film thickness and surface reactivity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Variation of cation stoichiometry is known to take place in perovskite thin films in many different circumstances, such as structural defects [26,67], strain relaxation [58,68] or near free surfaces [69,70]. For instance, cation segregation or exsolution were observed to generate regions with altered B/A ratio, which may affect the mobility and concentration of oxygen vacancies [71][72][73]. However, here we show that antisite defects may provide an efficient way to mitigate cationic nonstoichiometry effects on oxygen mass transport properties and that they should be considered when dealing with variation of the B/A ratio.…”
Section: Discussionmentioning
confidence: 99%